2011
DOI: 10.1177/0009922810393500
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin Dosing in Obese Pediatric Patients

Abstract: Since obesity did not alter vancomycin trough concentrations, overweight children should receive vancomycin based on actual body weight. However, since vancomycin troughs were substantially lower than those recommended for adults, further studies of vancomycin metabolism in children are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 13 publications
(15 reference statements)
1
27
0
2
Order By: Relevance
“…We present one of the largest cohorts published to date evaluating vancomycin, obesity, and nephrotoxicity [13][14][15][16][17][18][19][29][30][31]. Our study observed a 21% incidence of nephrotoxicity (obese = 18% vs. lean = 23%) among infectious episodes treated with vancomycin and a 12% incidence of new-onset hemodialysis (obese = 10% vs. lean = 14%).…”
Section: Discussionmentioning
confidence: 78%
“…We present one of the largest cohorts published to date evaluating vancomycin, obesity, and nephrotoxicity [13][14][15][16][17][18][19][29][30][31]. Our study observed a 21% incidence of nephrotoxicity (obese = 18% vs. lean = 23%) among infectious episodes treated with vancomycin and a 12% incidence of new-onset hemodialysis (obese = 10% vs. lean = 14%).…”
Section: Discussionmentioning
confidence: 78%
“…Data suggest dosage regimens be based on TBW, although obese patients may require more vigilant serum-level monitoring. [20][21][22][23] Pediatric studies have also recommended aminoglycoside dosage be based on either TBW or adjusted body weight.…”
Section: The Issuementioning
confidence: 99%
“…27 In obese adults, weight-adjusted V d was decreased, whereas weight-adjusted CL was either similar or decreased. 47 Pediatric studies did not yield significant conclusions regarding differences in weight-adjusted V d and CL.…”
Section: Introductionmentioning
confidence: 99%
“…47 Pediatric studies did not yield significant conclusions regarding differences in weight-adjusted V d and CL. 2,3,8,9 Notably, none of these pediatric PK studies used Bayesian analysis, which is better in predicting V d and CL in an obese population based on an understanding of the population PK properties and interindividual and intra-individual variability.…”
Section: Introductionmentioning
confidence: 99%